2014
DOI: 10.1093/icvts/ivu159
|View full text |Cite
|
Sign up to set email alerts
|

Who might benefit from early aspirin after coronary artery surgery?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether early administration of aspirin might optimize vein graft patency. More than 250 papers were found using the reported search, of which 4 new papers in addition to the previous 7 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Further, such studies would ideally weigh bleeding risks in light of potential effects on other serious outcomes. [ 50 , 51 ] These challenges highlight the need for, data-driven procedure-specific recommendations regarding postoperative NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…Further, such studies would ideally weigh bleeding risks in light of potential effects on other serious outcomes. [ 50 , 51 ] These challenges highlight the need for, data-driven procedure-specific recommendations regarding postoperative NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early (within 6 h) postoperative administration of aspirin is known to be beneficial for the patency rate of saphenous vein grafts 14) , our antiplatelet strategy may have exerted a favorable effect on the patency rate of saphenous vein grafts, and, in turn, had a more beneficial impact on the long-term outcomes of non-BITA patients than BITA patients. Although our results may not be compatible with earlier studies, it is important to note that in most previous studies that examined the effects of bilateral ITA use on long-term outcomes after CABG, conventional on-pump CABG was performed on most patients 4) 5)…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Gavaghan et al have been shown the largest risk reduction when aspirin administration starts at 1 hour after surgery; although this group had a non-significant higher rate of re-operation ( 8 ). However, in a study by Gukop et al have been stated that 6 hour after surgery is the ideal time for initiating aspirin administration, as long as bleeding has established ( 20 ).…”
Section: Discussionmentioning
confidence: 99%